Analysis of Aerodynamic Characteristics of the Rocket-Target for the „Stinger” System - Algimantas FEDARAVIČIUS (Wojskowa Akademia Techniczna, 2016)
This paper presents an analysis of aerodynamic characteristics of the rocket-target for the final training of shooting at aerial targets by the „Stinger” system service staff. The governing equations of fluid dynamics are presented and the computational model of airflow around the rocket is developed. ANSYS CFX computational fluid dynamics software is used to compute airflow velocities, pressure, the drag force and the drag coefficient. A practical implementation of the research is presented. Taking into account the simulation results, the rocket-target was designed and manufactured.
Keywords: Charakterystyki areordynamiczne pocisku rakietowego